1988
DOI: 10.1111/j.1476-5381.1988.tb11710.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by anti‐inflammatory agents of contraction induced by epidermal growth factor‐urogastrone in isolated longitudinal smooth muscle strips from guinea‐pig stomach

Abstract: 1 Epidermal growth factor-urogastrone (EGF-URO) caused a concentration-dependent contractile response of longitudinal muscle strips from the gastric body of the guinea-pig stomach. The contractile response to EGF-URO was monophasic, with tension returning rapidly to baseline. Desensitization was evident in that further addition of EGF-URO to the organ bath did not cause a second contraction. 2 Preincubation with indomethacin, ibuprofen, naproxen and aspirin markedly inhibited the contractions induced by EGF-UR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…1E). The concentrations of GS and Indo used were the maximal inhibitory concentrations of these two inhibitors in the gastric LM assay, as determined by concentration -inhibition curves obtained in previous work by us (Itoh et al 1988;Hollenberg 1994;Yang et id. 1993).…”
Section: Bp M a G Rmentioning
confidence: 99%
“…1E). The concentrations of GS and Indo used were the maximal inhibitory concentrations of these two inhibitors in the gastric LM assay, as determined by concentration -inhibition curves obtained in previous work by us (Itoh et al 1988;Hollenberg 1994;Yang et id. 1993).…”
Section: Bp M a G Rmentioning
confidence: 99%
“…However, compensative modulation of pulmonary vascular function by PKCι in PKCα -/- mice is unlikely, since pulmonary vascular hyperresponsiveness to U46619 was not reduced in PKCα -/- lungs following PKCι inhibition, as shown in this study. In line with this notion, it has been reported that treatment with the PKCι inhibitor sodium aurothiomalate failed to inhibit adrenaline-induced constriction of rat anterior mesenteric artery and vein [50] as well as epidermal growth factor-urogastrone-evoked contraction in isolated longitudinal smooth muscle strips from guinea-pig stomach [51]. Nevertheless, to our knowledge, this is the first report on the effects of selective PKCι inhibition on pulmonary vasoconstriction focusing on the specific response to U46619 in PKCα -/- lungs, so a potential PKCι-mediated modulation of pulmonary vascular function needs to be further evaluated in future studies.…”
Section: Discussionmentioning
confidence: 69%
“…Additionally, EGF-URO is known to exhibit a number of other biological activities, ranging from the stimulation of cellular calcium flux (Sawyer and Cohen, 1981) t o the modulation of smooth muscle contractility (Muramatsu et al, 1985Gan et al, 1990). In our own work, focused on the action in vitro of EGF-URO in smooth muscle systems, we have observed that in some preparations, derived from both vascular and non-vascular tissues, the contractile action of EGF-URO is entirely due to the production of prostanoids (Muramatsu et al, 1985Itoh et al, 1988;Pate1 et al, 1988). Thus, we have become interested to determine the mechanism(s) whereby EGF-URO stimulates the production of prostanoids in smooth muscle-derived cells; and we have turned our attention to focus on the effects of EGF-URO in smooth muscle-derived cell cultures.…”
mentioning
confidence: 99%